When the butterflies came - Little, Kimberley Griffiths (New York, N.Y. : Scholastic Press, 2013)
Tara Doucet is grieving for her grandmother, and her family is falling apart around her, but it seems like her grandmother has preplanned an elaborate itinerary for her to follow which will lead her and her sister Riley from Louisiana to a South Pacific island and into danger--and everywhere she turns butterflies follow.
Keywords: Butterflies; Grandmothers; Sisters; Bereavement; Butterflies; Grandmothers; Sisters; Grief; Mystery and detective stories